The Films of the Eighties: A Complete, Qualitative Filmography to Over 3400 Feature-Length English Language Films, Theatrical and Video-Only, Released Between January 1, 1980, and December 31, 1989 - Nowlan, Robert A.; Nowlan, Gwendolyn Wright (McFarland & Co., 1991)
Keywords: Catalogs; Motion pictures; dept.ils; dept.mat; faculty_collection

Evaluating Library Buildings: Principles and Procedures for Post-Occupancy Evaluation - Kusack, James M. (Connecticut State Library, 1991)
Keywords: Evaluation; Library architecture; Library buildings; United States; dept.ils; faculty_collection

The Design and Evaluation of Public Library Buildings - Lushington, Nolan; Kusack, James M. (Library Professional Publications, 1991)
Keywords: Evaluation; Library buildings; Library architecture; Public libraries; dept.ils; faculty_collection

The information quest as resolution of uncertainty: Some approaches to the problem - Sieving, P.C. (Information Seeking and Communicating Behavior of Scientists and Engineers, 1991)
The ideal user of scientific and technical information: shall we design one? The positive personality traits one would wish for in a spouse would do nicely for a start: patient; thoughtful; caring; able to see our (the librarians') virtues through the fog of early-morning not yet-wakefulness or late evening exhaustion; able to communicate needs and wants clearly and without a lot of emotional overtones; willing to work hard to obtain desired results; and apprecia tive of what We (librarians) do. Add to this other talents which, while useful, are less often associated with marriage: the ability to understand and retain complex organizational details; patience with less-than-perfect systems; an intuitive understanding of how information is organized; and a sense of how best to cope with the inter-face between the deluge of possible information resources and the limited needs of one particular user (not to mention limited capacities for retaining and controlling that information flood once the gates are open). © 1991 by The Haworth Press, Inc. All rights reserved.
Keywords: dept.ils